Evaluasi Pembelajaran Daring Pascapandemi: Menuju Model Hybrid Learning di Perguruan Tinggi - Afdawaiza, Afdawaiza (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
The digital transformation of higher education has accelerated significantly since the COVID-19 pandemic and continues to evolve in the post-pandemic era. This study aims to evaluate the implementation of online learning and to formulate strategic policy directions toward sustainable hybrid learning models. Employing a quantitative descriptive approach, this research utilizes primary data collected from 160 respondents, consisting of students and lecturers at the Faculty of Islamic Economics and Business, UIN Sunan Kalijaga Yogyakarta. The findings indicate that synchronous learning platforms such as Zoom and Google Meet are perceived as effective in supporting online learning; however, challenges remain in terms of interaction quality, student engagement, and the achievement of learning outcomes. Advanced statistical analysis reveals that perceived usefulness, quality of teaching materials, ease of use, and learning interaction significantly influence student satisfaction and learning outcomes, with learning interest acting as a mediating variable. Grounded in the integration of TPACK, TAM, and UTAUT frameworks, this study highlights that successful digital learning transformation requires not only technological adoption but also pedagogical innovation and institutional support. The study concludes that hybrid learning represents a strategic direction for higher education institutions to enhance learning quality and sustainability in the digital era.